Circular Communities The circular value flower as a design method for collectively closing resource flows - Smit, Mo (TU Delft Open, 2023)
In Circular Communities, pioneering, collectively supported initiatives that are aimed at closing resource cycles at neighbourhood level take a central position. They are all examples of initiatives that contribute to the transition to a circular economy. For the analysis of these different circular initiatives, the researchers - urban designer Els Leclercq and architect Mo Smit - developed a unique method: the Circular Value Flower method. This method helps to organize the collective closing of resource cycles (bio and tech materials, energy, water and nutrients) on a neighbourhood scale and provides insight into the added value (social, ecological, aesthetic, cultural and economic) that can be realized within the built environment. Circular Communities offers inspiration and lessons for integral sustainable interventions at the scale of the neighbourhood and ties in with the new Dutch Environmental Planning Act, which explicitly offers room for citizen initiatives and local commissioning in the Netherlands.